2014
DOI: 10.1111/ajd.12232
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of Dowling‐Degos disease using intense pulsed light

Abstract: Dowling-Degos disease (DDD) is a rare inherited pigmentary disorder characterised by reticulate pigmentation at flexural sites. No treatment modality has yet been established as a definitive method for the effective elimination of lentigines in DDD. We present a case of a 24-year old woman with DDD treated successfully using intense pulsed light as a novel management strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 6 publications
(12 reference statements)
0
4
0
1
Order By: Relevance
“…Another study reported that using a fractional Er:YAG laser led to improvement of pigmentation in facial lesions of an Asian patient with DDD and was effective in reducing postoperative inflammation but could not produce the therapeutic results of an ablative approach . Recently, one case report showed that the pigmentation of lentigines in patients with DDD could be treated successfully using intense pulsed light, suggesting an alternative option for pigmented lesions in DDD …”
Section: The Spectrum Of Dowling‐degos Diseasementioning
confidence: 99%
“…Another study reported that using a fractional Er:YAG laser led to improvement of pigmentation in facial lesions of an Asian patient with DDD and was effective in reducing postoperative inflammation but could not produce the therapeutic results of an ablative approach . Recently, one case report showed that the pigmentation of lentigines in patients with DDD could be treated successfully using intense pulsed light, suggesting an alternative option for pigmented lesions in DDD …”
Section: The Spectrum Of Dowling‐degos Diseasementioning
confidence: 99%
“…Laser treatment appears to be promising. Both ablative and fractional Er:YAG laser [24,25] as well as high-energy flash lamps [26] have already been used successfully in patients with Dowling-Degos disease. These are, however, case reports.…”
Section: Discussionmentioning
confidence: 99%
“…6 Laser treatments; especially CO2, Er:YAG, Nd:YAG have been reported in the literature with variable results. [10][11][12][13] Wenzel et al reported a case of DDD efficaciously treated using an ablative Er:YAG laser; however, their follow-up was only 2.5 years, and it was not clear whether the results were permanent. Adverse effects were not reported.…”
Section: Discussionmentioning
confidence: 99%